Wittgenstein and the End of Philosophy? (Global Journal of Human-Social Science, 2021)
This paper's aim is to critically analyze Wittgenstein's arguments against traditional philosophy. It is possible to identify three arguments against it in Wittgenstein's work: (1) The tractarian critique of the metaphysical necessary propositions, (2) the critique of the conception of real definition in the PI and (3) the problem of the role of the ideal, or the problem of dogmatism. By analyzing these three arguments we intend to show that none of them implies necessarily that we should abandon any positive conception of philosophy and stick to a negative analytical one as Wittgenstein understands it.
Keywords: wittgenstein; philosophy; metaphysics